Caribbean tertiary education system : a review and proposals for future directions - Sangster, A. W. (Caricom Secretariat GeorgetownGY, 1997)
Attempts to address some of the critical concerns of the region and looks at the way forward. Focuses on the status of and development in the tertiary and higher education sector. Examines the financing of the system.